High‐Performance Overall CO2 Splitting on Hierarchical Structured Cobalt Disulfide with Partially Removed Sulfur Edges. (11th May 2020) - Han, Zhen; Hu, Qi; Cheng, Zhong; Li, Guomin; Huang, Xiaowan; Wang, Ziyu; Yang, Hengpan; Ren, Xiangzhong; Zhang, Qianling; Liu, Jianhong; He, Chuanxin
Abstract: The ability to develop bifunctional electrocatalysts for concurrent CO2 reduction reaction (CO2 RR) and oxygen evolution reaction (OER) is the key to the practical application of CO2 splitting to produce CO. However, this remains a grand challenge. Herein, a robust strategy to rationally craft hierarchical structured bifunctional electrocatalysts composed of 3D CoS2 nanocages interconnected on 2D CoS2 nanosheet arrays (denoted hierarchical CoS2 nanocages) for high‐performance CO2 splitting is developed. The subsequent calcination removes the partial S edges of CoS2, thereby strongly suppressing the hydrogen evolution reaction (HER) of CoS2 . By combining theoretic and experimental results, for the first time, it is discovered that the plane S of CoS2, instead of S edges, are highly active for CO2 RR but inactive for HER, rendering the plane S as ideal active sites for CO2 RR. Intriguingly, the composition tuning via calcination and the presence of a hierarchical architecture confer hierarchical CoS2 nanocages respective outstanding CO2 RR and OER performance. Notably, the hierarchical CoS2 nanocages can be exploited as bifunctional electrocatalysts for overall CO2 splitting to yield the current density of 1 mA cm −2 at a small cell voltage of 1.92 V, much lower than the widely reported values (>2.5 V). Abstract : A facile yet robust route is developed for crafting hierarchically structured Co disulfide (CoS2 ) nanomaterials (i.e., 3D nanocages/2D nanosheet arrays). After removing S edges for strongly suppressing hydrogen evolution, the hierarchical CoS2 displays outstanding performance for overall CO2 splitting.